LITAF (Lipopolysaccharide-Induced Tumor Necrosis Factor) Regulates Cardiac L-Type Calcium Channels by Modulating NEDD (Neural Precursor Cell Expressed Developmentally Downregulated Protein) 4-1 Ubiquitin Ligase. (September 2019) - Moshal, Karni S.; Roder, Karim; Kabakov, Anatoli Y.; Werdich, Andreas A.; Chiang, David Yi-Eng; Turan, Nilüfer N.; Xie, An; Kim, Tae Yun; Cooper, Leroy L.; Lu, Yichun; Zhong, Mingwang; Li, Weiyan; et al.
Abstract : Background: The turnover of cardiac ion channels underlying action potential duration is regulated by ubiquitination. Genome-wide association studies of QT interval identified several single-nucleotide polymorphisms located in or near genes involved in protein ubiquitination. A genetic variant upstream of LITAF (lipopolysaccharide-induced tumor necrosis factor) gene prompted us to determine its role in modulating cardiac excitation. Methods: Optical mapping was performed in zebrafish hearts to determine Ca 2+ transients. Live-cell confocal calcium imaging was performed on adult rabbit cardiomyocytes to determine intracellular Ca 2+ handling. L-type calcium channel (LTCC) current ( I Ca, L ) was measured using whole-cell recording. To study the effect of LITAF on Cav1.2 (L-type voltage-gated calcium channel 1.2) channel expression, surface biotinylation, and Westerns were performed. LITAF interactions were studied using coimmunoprecipitation and in situ proximity ligation assay. Results: LITAF knockdown in zebrafish resulted in a robust increase in calcium transients. Overexpressed LITAF in 3-week-old rabbit cardiomyocytes resulted in a decrease in I Ca, L and Cavα1c abundance, whereas LITAF knockdown increased I Ca, L and Cavα1c protein. LITAF-overexpressing decreases calcium transients in adult rabbit cardiomyocytes, which was associated with lower Cavα1c levels. In tsA201 cells, overexpressed LITAF downregulated total and surface pools of Cavα1c via increased Cavα1c ubiquitination and its subsequent lysosomal degradation. We observed colocalization between LITAF and LTCC in tsA201 and cardiomyocytes. In tsA201, NEDD (neural precursor cell expressed developmentally downregulated protein ) 4-1, but not its catalytically inactive form NEDD4-1-C867A, increased Cavα1c ubiquitination. Cavα1c ubiquitination was further increased by coexpressed LITAF and NEDD4-1 but not NEDD4-1-C867A. NEDD4-1 knockdown abolished the negative effect of LITAF on I Ca, L and Cavα1c levels in 3-week-old rabbit cardiomyocytes. Computer simulations demonstrated that a decrease of I Ca, L current associated with LITAF overexpression simultaneously shortened action potential duration and decreased calcium transients in rabbit cardiomyocytes. Conclusions: LITAF acts as an adaptor protein promoting NEDD4-1–mediated ubiquitination and subsequent degradation of LTCC, thereby controlling LTCC membrane levels and function and thus cardiac excitation. Abstract : Supplemental Digital Content is available in the text.